Effective Techniques for Wireless Charging for Unmanned Aerial Vehicles (UAV) - Nair, Sheeja; Shetty, Ashwin; Maurya, Niraj; Scurtu, Ionut Cristian (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Unmanned aerial vehicles are devices that can operate in air without any external human interference, thus making them completely autonomous. These devices are crucial for security surveillance and various payload services. The main aim in this paper will be to discuss the scope of wireless charging for such unmanned aerial vehicles (UAV) or simply speaking drones/quad copters and to come up with the ways to efficiently implement the above aim using readily available Wireless Power Transfer (WPT) modules and components. Three methods with their advantages, drawbacks and overall efficiency is considered. Method 1 will focus on implementing wireless power transmission using readily available modules like XKT-801. Method 2 will show the implementation of WPT using a Flyback transmission topology. Method 3 explores the usage of a Full bridge transmission for WPT.